Employer-mandated obstructive sleep apnea treatment and healthcare cost savings among truckers. Issue 4 (24th October 2019) - Burks, Stephen V; Anderson, Jon E; Panda, Bibhudutta; Haider, Rebecca; Ginader, Tim; Sandback, Nicole; Pokutnaya, Darya; Toso, Derek; Hughes, Natalie; Haider, Humza S; Brockman, Resa; Toll, Alice; et al.
Abstract: Objective: To evaluate the effect of an employer-mandated obstructive sleep apnea (OSA) diagnosis and treatment program on non-OSA-program trucker medical insurance claim costs. Methods: Retrospective cohort analysis; cohorts constructed by matching (randomly, with replacement) Screen-positive Controls (drivers with insurance screened as likely to have OSA, but not yet diagnosed) with Diagnosed drivers ( n = 1, 516; cases = 1, 224, OSA Negatives = 292), on two factors affecting exposure to medical claims: experience level at hire and weeks of job tenure at the Diagnosed driver's polysomnogram (PSG) date (the "matching date"). All cases received auto-adjusting positive airway pressure (APAP) treatment and were grouped by objective treatment adherence data: any "Positive Adherence" ( n = 932) versus "No Adherence" ( n = 292). Bootstrap resampling produced a difference-in-differences estimate of aggregate non-OSA-program medical insurance claim cost savings for 100 Diagnosed drivers as compared to 100 Screen-positive Controls before and after the PSG/matching date, over an 18-month period. A two-part multivariate statistical model was used to set exposures and demographics/anthropometrics equal across sub-groups, and to generate a difference-in-differences comparison across periods that identified the effect of OSA treatment on per-member per-month (PMPM) costs of an individual driver, separately from cost differences associated with adherence choice. Results: Eighteen-month non-OSA-program medical claim costs savings from diagnosing (and treating as required) 100 Screen-positive Controls: $153, 042 (95% CI: −$5, 352, $330, 525). Model-estimated effect of treatment on those adhering to APAP: −$441 PMPM (95% CI: −$861, −$21). Conclusions: Results suggest a carrier-based mandatory OSA program generates substantial savings in non-OSA-program medical insurance claim costs.